THE NON-COOPERATIVE JOURNALISTS’ STRUGGLE AGAINST SELF-CENSORSHIP DURING THE NEW ORDER INDONESIA (1967-1998) - Wina Sumiati (Metahumaniora, 2020)
In the Soeharto era, the Indonesian journalists were divided into two categories: the cooperative and the non-cooperative ones. Different from the former that obeyed to the government to do self-censorship, the latter category challenged against the government by publishing not only good news, but also any sensitive news about the national problems. In this research, I will analyze the struggle of the non-cooperative journalists, later called the independent journalists, against the regulation of censorship. How they responded to the censorship, and what ways they used to resist the regulation will be the main focuses of the study. In conducting this research, I use history method including heuristic, criticism, interpretation, and historiography. The result of the study shows that the independent journalists took actions by founding an organization called the AJI (the Alliance of Independent Journalists) to organize the journalists with the same goal: ceasing freedom of expression. They also had several alternative media to disseminate the information to avoid the government surveillance, like publishing books, using the internet, conducting seminars, and founding discussion forums with Indonesian students. Their efforts, triggered by the economic collapse factor, succeeded to end the authoritarianism regime.